2013
DOI: 10.1007/s11225-013-9483-6
|View full text |Cite
|
Sign up to set email alerts
|

Complexity Results for Modal Dependence Logic

Abstract: Modal dependence logic was introduced recently by Väänänen. It enhances the basic modal language by an operator =(). For propositional variables p 1 , . . . , p n , =(p 1 , . . . , p n−1 , p n ) intuitively states that the value of p n is determined by those of p 1 , . . . , p n−1 . Sevenster (J. Logic and Computation, 2009) showed that satisfiability for modal dependence logic is complete for nondeterministic exponential time.In this paper we consider fragments of modal dependence logic obtained by restrictin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…In (Grädel, 2012), it was also shown that, for the fragment of D with constancy atoms only, the model checking problem is PSPACE-complete. For modal versions of dependence logic, the model checking problem has been studied in (Ebbing and Lohmann, 2012) and , and the satisfiability problem in (Lohmann and Vollmer, 2013) and (Sevenster, 2009).…”
Section: Complexity Results For Dependence Logicmentioning
confidence: 99%
See 1 more Smart Citation
“…In (Grädel, 2012), it was also shown that, for the fragment of D with constancy atoms only, the model checking problem is PSPACE-complete. For modal versions of dependence logic, the model checking problem has been studied in (Ebbing and Lohmann, 2012) and , and the satisfiability problem in (Lohmann and Vollmer, 2013) and (Sevenster, 2009).…”
Section: Complexity Results For Dependence Logicmentioning
confidence: 99%
“…The semantics of MDL is defined with respect to sets of worlds in a frame (Kripke structure). Modal dependence logic has been further studied in (Sevenster, 2009;Lohmann, 2012;Ebbing and Lohmann, 2012), and (Lohmann and Vollmer, 2013). Also, the extension of MDL by the intuitionistic implication has been studied in .…”
Section: Some Variants and Extensions Of Dependence Logicmentioning
confidence: 99%
“…where each α i is a classical formula. This normal form is a generalization of a similar normal form for InqL defined in [5,6], and similar disjunctive normal forms for modal dependence logics without intuitionistic implication were discussed in the literature with a slightly different presentation (see e.g., [12,19]). Let us now introduce our disjunctive normal form for MT 0 as a recursively defined translation τ(φ) for every formula φ of MT 0 :…”
Section: Proofmentioning
confidence: 96%
“…Basic model-theoretic properties of the logics were studied in e.g., [26], a van Benthem Theorem for the logics was proved in [16], and the frame definability of the logics was studied in [24,25]. The expressive power and the relevant computation complexity problems of the logics were investigated extensively in e.g., [7,8,9,12,19,20,26]. In this paper, we study two problems that received less attention in the literature, namely the axiomatization problem and the comparison between team semantics and the single-world semantics.…”
mentioning
confidence: 99%
“…From a computational complexity perspective, DL is well understood: most of the possible operator fragments have been classified [16,17]. However, it turned out that model checking and satisfiability for propositional dependence logic PDL are already NP-complete [10,24]. As a result, tractable enumeration of solutions in the full logic is impossible (unless P and NP coincide) and we focus on a fragment of PDL which we will call, for historical reasons, the Poor Man's fragment [18].…”
Section: Introductionmentioning
confidence: 99%